Weaving Relationships Between Education and Health: the process of schooling of seriously ill students - Covic, Amália Neide; de Melo Oliveira, Fabiana Aparecida; Zecchin Vistor, Victor Gottardello; Covic Bastos, André (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2018)
The objective of this study is research produced by the multi-professional group of Education and Health in a center for the care of children and adolescents with cancer in a Brazilian city. We selected an investigation that aims to study and determine the school specificities of pupils submitted to hematopoietic cell transplantation (HCT). We studied the process of school intervention with 200 student-patients, in the interval of 2000-2015. Four annotations were made for the articulation of knowledge focused on the social practices of language of the current school year. The students submitted to the HCT present a process of irregular schooling necessitating orientation to the specific curricular demands.